Effects of leaves of Ipomoea batatas (Convolvulaceae) on nest development and on respiratory metabolism of leaf-cutting ants Atta sexdens L. (Hym., Formicidae) - Hebling, MJA; Bueno, O. C.; Maroti, P. S.; Pagnocca, F. C.; da Silva, O. A. (Blackwell Wissenschafts Verlag Gmbh, 2000)
Laboratory colonies of the leaf-cutting ants Atta sexdens feed daily with leaves of Ipomoea batatas showed ant mortality and a significant decrease in the size of the fungal garden after the second week, with complete depletion of nests after 5 weeks of treatment. The mean oxygen consumption rate of these ants was higher than the control (ants collected from nests feed with leaves of Eucalyptus alba), suggesting a physiological action of the leaves of I. batatas on the ants in addition to the effect of inhibiting the growth of the fungal garden.